Introduction to forestry science - Burton, L. DeVere (Albany, NY : Delmar Publishers, 1998)
A senior high textbook focusing on the North American forest regions; classification, anatomy, and diseases of trees; forest management and products; and urban forestry.
Includes index.
Keywords: Forests and forestry -- North America -- Juvenile literature; Forest management -- United States -- Juvenile literature; Forests and forestry -- Juvenile literature; Forest management -- Juvenile literature; Forests and forestry; Forest management